Balancing food security and environmental sustainability by optimizing seasonal-spatial crop production in Bangladesh - Man Li; Guo, Zhe; Zhang, Wei (IOP Publishing, 2021)
The intensification of crop production has been identified as one of the major drivers of environmental degradation. While significant advances could still be made with more widespread adoption of sustainable intensification technologies that address the agronomic efficiency of nitrogen fertilizers, the dynamic use of agricultural land across seasons and associated crop-specific responses to fertilizer applications have so far been largely overlooked. This paper explores the potential for improving the economic-environmental performance of crop production through spatially integrated modeling and optimization, as applied to Bangladesh. Results show that per-billion-Taka nitrogen loss from soil would decline by 83% from the baseline level through factoring in crop-specific, seasonal and spatial variations in crop nitrogen-use efficiency and nitrogen transport. The approach should complement other policy analysis and decision-support tools to assess alternative options for maximizing the positive outcomes of nitrogen fertilizers with regard to farm income and food security, while maintaining environmental sustainability.